ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN LANSIA DI KECAMATAN SUKAWATI KABUPATEN GIANYAR - Ginanto, I Kadek Adi; Sudibia, Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009], 2022)
The aims the study analyze effect marital status, employment status, education level, level religiosity simultaneously and partially welfare of the elderly in Sukawati District. Research on elderly in Sukawati District focused two villages, namely Batubulan and Sukawati Village with total sample 151 people. Sampling was done combining purposive sampling and accidental sampling and data analysis using multiple linear regression. The results of this study marital status, employment status, education level, level of religiosity have a simultaneous and significant effect on the welfare of the elderly in Sukawati District, Gianyar Regency. Marital status, employment status, education level, level of religiosity have a partially significant positive effect on the welfare of the elderly in Sukawati District, Gianyar Regency. Keywords: marital status, employment status, education level, religiosity level, elderly welfare.